The Importance of Parents Support in Student Learning Problems - Nurul Novia; Yusri Yusri; Yeni Karneli; Verlanda Yuca (Jurnal Neo Konseling, 2020)
The implementation of the teaching and learning process is inseparable from various learning problems. In the problems experienced by students need to be created an atmosphere of active learning. One factor is the family environment. The relationship between parent and child has a very big influence on children's learning outcomes. Therefore, problems or obstacles experienced by children can be influenced by parents. There’s till found learning problems of children caused by lack of parental support. So it can be concluded the relationship of parental support with learning problems is the provision of support provided by parents such as student interaction or communication with parents. For advice this issue is a good relationship between parents and children. And also parental care is needed in shaping learning skills. This paper will describe the form of learning problems and aspects of parental support and their implications in guidance and counseling.